Rapid composting of food waste and yard waste with effective microorganisms (EM). Issue 1 (November 2021) - Zakarya, I A; Izhar, T N T; Noordin, N M; Ibrahim, N; Kamaruddin, S A
Abstract: Rapid composting is an alternative method to reduce highly generated food waste and yard waste discarded to the landfill. This study aims to determine the effect of effective microorganisms (EM) application on the chemical and physical properties and to determine the performance and factors affecting the rapid composting process. The chemical and physical properties such as pH, temperature, moisture content, carbon-to-nitrogen (C/N) ratio and Nitrogen (N), phosphorus (P) and Potassium (K) nutrient are examined over rapid composting period in order to assess the performance of compost and effectiveness of EM in enhancing the degradation process of organic waste. There are three compost prepared which are A, B and C that received different ratio of EM which 1 L, 2 L and 3 L respectively. Based on the result obtained from the 54 days of composting conducted, compost A, B and C show no significance differences on parameters tested. The temperature obtained mostly within the range 35-38 °C, pH values are 5-9, moisture content are 20-60 % and for NPK nutrient, Total Nitrogen content are 1.3 % to 1.4 %, Total Phosphorus are within 0.10 ppm to 0.45 ppm and Potassium are within 0.8 ppm to 6.7 ppm.